Mortgage Lending in Boston: Interpreting HMDA Data - Munnell, Alicia H.; Tootell, Geoffrey M. B.; Browne, Lynn E.; McEneaney, James P. (American Economic Review, 1992)
The Home Mortgage Disclosure Act was enacted to monitor minority and low-income access to the mortgage market. The data collected for this purpose show that minorities are more than twice as likely to be denied a mortgage as whites. Yet variables correlated with both race and creditworthiness were omitted from these data, making any conclusion about race's role in mortgage lending impossible. The Federal Reserve Bank of Boston collected additional variables important to the mortgage lending decision and found that race continued to play an important, though significantly diminished, role in the decision to grant a mortgage. Copyright 1996 by American Economic Association.